2018
DOI: 10.1111/ggi.13248
|View full text |Cite
|
Sign up to set email alerts
|

Resident and facility characteristics associated with care‐need level deterioration in long‐term care welfare facilities in Japan

Abstract: Aim: To determine the resident and facility characteristics associated with residents' care-need level deterioration in long-term care welfare facilities in Japan.Methods: A nationally representative sample of 358 886 residents who lived in 3774 long-term care welfare facilities for at least 1 year from October 2012 was obtained from long-term care insurance claims data. Facility characteristics were linked with a survey of institutions and establishments for long-term care in 2012. We used a multilevel logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 21 publications
1
25
0
1
Order By: Relevance
“…Insurers can consider and counteract the most important factors that contributed to the increases in care needs in an individual's CNL. 23 Consistent with previous research, 10,[25][26][27][28] this present study identified age as the most important factor related to increases in care needs. Other factors identified as important to the ML model were related to medical service use, excretion ability, daily hygiene, previous CNL, and bedridden Level 8.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Insurers can consider and counteract the most important factors that contributed to the increases in care needs in an individual's CNL. 23 Consistent with previous research, 10,[25][26][27][28] this present study identified age as the most important factor related to increases in care needs. Other factors identified as important to the ML model were related to medical service use, excretion ability, daily hygiene, previous CNL, and bedridden Level 8.…”
Section: Discussionsupporting
confidence: 89%
“…9 Previous studies have categorized the patterns and trajectories of care needs 4 and investigated factors related to changes in care needs. [8][9][10] Most of the studies have applied traditional statistical methods to develop regression models that successfully express factors related to changes in CNLs. However, they have not been able to predict the increasing care needs of each insured.…”
Section: Introductionmentioning
confidence: 99%
“…First, the finding that the LTCI‐CNLs classification, an index of an objective assessment of care burden, has a moderate correlation with WHODAS 2.0 and SARC‐F scores suggests that the LTCI‐CNLs classification can be used as a proxy for determining perceived difficulty functioning in daily life and physical performance in patients who are cognitively functional enough to answer these questions. As the LTCI‐CNLs classification is a standardized index incorporated into the Japanese public long‐term insurance system, the LTCI‐CNLs classification could be used in several ways to improve health policy decision‐making and health service research 1,4,18,19 . For health service research, the LTCI‐CNLs classification could be used for casemix adjustment; 18 for example, to examine the effectiveness of specific medical procedures, such as management of oral hygiene, on mortality among older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies using single LTC claims highlighted the lack of information on detailed medical conditions (11)(12)(13)(14)(15). The reason was the difficulty in investigating the effect of LTC service uses without adjusting for the medical conditions of older people.…”
Section: Discussion Of Current Status and Perspectives Of Ltc Claims Analysismentioning
confidence: 99%